THЕ IMPОRTАNCЕ ОF UZBЕK CUMULАTIVЕ TАLЕS IN THЕ STUDY ОF THЕ FОLKLОRЕ ОF TURKIC PЕОPLЕS (TAMADDUN NURI JURNALI, 2025)
This article is dedicated to the study of cumulative tales, which are an important part of Uzbek folk oral literature, using a holistic methodology. Additionally, with the help of a holistic methodology, the structure and semantic features of these tales are thoroughly examined, and their folkloristic value is assessed.